ALIGNING THE ACTIVITIES OF ARCHIVAL INSTITUTIONS IN THE EUROPEAN UNION MEMBER STATES - LUKŠAITĖ, DAIVA (Knygotyra, 2014)
This article reveals the work of DLM forum, the European Board of National Archivists and the European Archives Group. It also identifies issues concerning documents and the field of archives management as well as suggested ways of problem solving. The coordination of cooperation among the archives institutions in the EU plays a great role while forming the common policy of document and archives management as well as methods and practice applied by archives institutions. In this way the coordination contributes to both preservation of the European documentary heritage and a more transparent activity of archives institutions.The article comes to the conclusion that at the turn of the 21st century in the aftermath of EU enlargement EU institutions reacted to the demand for tightening the archival activities of the EU member states. The European Archives Group was established in order to coordinate the cooperation in the field of archives. The importance of the European Board of National Archivists has been officially recognised and the Board goes on promoting the cooperation among archives institutions while solving common issues. It is also of great importance that the spheres and challenges have been pointed out on the initiative of the institutions themselves. DLM forum, EBNA and EAG align their actions and seek effective and appropriate solutions. International projects e.g. (APEx project) contributes to documents description kept in archives as well as to the equalization of international information exchange practice. International working groups have been made up, the public announcement of their activity results ensures timely sharing of both the accumulated knowledge as well as good practice. Since 2011 the Office of the Chief Archivist of Lithuania as well as state archives, EBNA, EAG and DLM forum members have been represented at a larger scale and this might be related to the preparation for the Lithuanian presidency of the EU Council. The Office of the Chief Archivist of Lithuania was responsible for the meetings of EBNA, EAG and DLM forum which are considered to be informal expert meetings and were organised in the second half of 2013. The Office of the Chief Archivist of Lithuania also seeks a wider Lithuanian representation at such institutions.